Klotho (rs1207568 and rs564481) gene variants and colorectal cancer risk - Kamal, Asmaa; Salama, Mohamed; Kamal, Amr; Mohsen, Ahmed; Siam, Ibrahem (Turkish Journal of Gastroenterology, 2020)
Background/Aims: Colorectal cancer is the third commonest cancer worldwide, klotho gene was reported as a tumor suppressor gene, therefore the aim of the present study was to investigate the association between klotho (rs1207568 and rs564481) variants and colorectal cancer (CRC) in Egyptian patients. Materials and Methods: A case-control study comprising 100 patients with CRC and 100 age- and sex-matched healthy controls. Genotyping of klotho was performed by polymerase chain reaction with confronting two-pair primers (PCR-CTPP). Results: The frequencies of the A allele of rs1207568 and the AC haplotype were significantly higher in the CRC patients than in the controls (p=0.019 and 0.005, respectively). Conclusion: We propose that klotho (rs1207568 and rs564481) variants play a significant role in colorectal carcinogenesis and that the klotho protein could be a target for oncotherapy.